New Approaches to Synthetic Organic Chemistry - Darabantu, Mircea; Rinderspacher, Alison; Proni, Gloria (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The "New Approaches to Synthetic Organic Chemistry" Special Issue has continued to challenge and expand our scientific knowledge of the surrounding world, exploring the frontiers between at least two of its dynamic interfaces: human life and the environment. Subject to all evolutionary facets of organic chemistry, its perpetual developments reimagined within the current organic synthesis (strategies, methodologies, reaction mechanisms, reagents, catalysts, chemical and instrumental auxiliaries) nevertheless obey two crucial common denominators, "selectivity" vs. "specificity" (these terms being, equally, preceded by typical prefixes, either chemo-, regio- or stereo-), as mandatory criteria. The present Special Issue gathered research articles, communications, and review papers, disclosing the most recent advances in organic synthesis, i.e., those related to its near future defined as "atomic precision" in chemical reactions. The sustainability of these efforts, which denotes an intrinsic chemical diversity, is expected to highlight, to the interested readers, their innovative applications in human life and the environment.